Anarchist voices : an oral history of anarchism in America - Avrich, Paul (Princeton University Press, 1996)
Through his many books on the history of anarchism, Paul Avrich has done much to dispel the public's conception of the anarchists as mere terrorists. In Anarchist Voices, Avrich lets American anarchists speak for themselves. This abridged edition contains fifty-three interviews conducted by Avrich over a period of thirty years, interviews that portray the human dimensions of a movement much maligned by the authorities and contemporary journalists. Most of the interviewees (anarchists as well as their friends and relatives) were active during the heyday of the movement, between the 1880s and the 1930s. They represent all schools of anarchism and include both famous figures and minor ones, previously overlooked by most historians.--From publisher description.